Hydrogen induced amorphization of LaMgNi4 phase in metal hydride alloys. (3rd August 2015) - Young, K.; Ouchi, T.; Shen, H.; Bendersky, L.A.
Abstract: Hydrogen induced amorphization (HIA) of the LaMgNi4 phase at 30 °C was found in three LaMgNi4 /LaNi5 two-phase metal hydride (MH)-forming alloys. The amorphization happened at the first dehydrogenation cycle from a fully hydrided alloy, and the process is reversible after annealing at 250 °C for 1 h. The hydrogen storage capacity of the LaMgNi4 phase in an amorphous state is higher than in its crystalline form. A scanning electron microscope study did not observe any significant changes in the shape of grains as a consequence of HIA and re-crystallization. A transmission electron microscope study confirmed the amorphous structure of the LaMgNi4 phase after HIA. These findings suggest a new way to improve the performance of MH alloys when used in electrochemical applications. Highlights: Hydrogen intruded amorphization in LaMgNi4 phase is found at room temperature. The amorphized LaMgNi4 phase returns to micro-crystalline after annealing. The amorphized LaMgNi4 phase has a higher hydrogen storage capacity. TEM confirms an amorphous structure with nano-crystallites.